EXPEDIENTE - Tude de Sá, Alzira Gondim (PontodeAcesso, 2015)
Presidente do Comitê EditorialLídia Maria Batista Brandão Toutain EditorLídia Maria Batista Brandão Toutain Alzira Gondim Tude de Sá, UFBA/ICI Editor ExecutivoSérgio Franklin, UFBA/ICI, Brasil NormalizaçãoKátia Rodrigues Oliveira, UFBA Maria Isabel Sousa barreiras, UFBA, Brasil Consultora EditorialFlavia Goulart Mota Garcia Rosa, UFBA, BrasilConsultor de TIRodrigo França Meirelles, UFBA, BrasilConselho Editorial NacionalDulce Amélia B. Neves, Universidade Federal da Paraíba Elmira Luzia Melo Soares Simeão, UnB, Brasil Hélio Kuramoto, IBICT, Estados Unidos da América do Norte Luis Fernando Sayão, CNEN/CIN Luis Milanesi, ECA Maria Regina Marteleto, IBICT/ECO/UFRJ, Brasil Marilene Lobo Abreu Nanci Oddone, ICI Rosali Fernandez de Souza, UFF Ursula Blattmann, Universidade Federal de Santa Catarina, Brasil Conselho Editorial InternacionalJosé António Frías, Universidad de Salamanca, Espanha Margarida Medeiros, Portugal Miguel Ángel Márdero Arellano, IBICT, Brasil Moreiro González José Antonio, Universidad Carlos III de Madrid, Espanha Peter Burke, Reino Unido Colaborador CientíficoHenriette Ferreira Gomes, UFBA, Brasil